ANALISIS PENGARUH BRAND AWARENESS, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Produk Deterjen Merek BOOM di Kabupaten Bojonegoro) - Najib, Muhammad Alfiyan; Soesanto, Harry; Sukresna, I Made (Master of Management Diponegoro University, 2016)
The purpose of this research are to analyze the factors that influence brand awareness and perceived value and influence on purchase decisions detergent BOOM in Bojonegoro. The object of this research is that consumers detergent BOOM in Bojonegoro. There are 105 respondents and this research used purposive sampling technic.The data analyze technic which used in this case is the structural equation model (SEM) by AMOS 24 software. The result using SEM showed that criteria goodness of fit full model ischi-square= 184 471, probability = 0.279, CMIN / DF = 1.080, GFI = 0.889, AGFI = 0.825, TLI = 0.990, CFI = 0.992, and RMSEA = 0.024. The results said that the models in this research can be used.The results showed that sales promotion has a positive and significant effect on brand awareness, advertising effectiveness does not have effect on brand awareness, brand image has a positive and significant effect on the perceived value, perceived quality has a positive and significant effect on the perceived value, brand awareness does not have effect on purchase decision, perceived value has a positive and significant effect on purchase decision.According to this research, there are a few limitation on this research and upcoming research’s agenda that can be done in the next research.